Participating in extracurricular activities and school sports during the COVID-19 pandemic: Associations with child and youth mental health - LaForge-MacKenzie, Kaitlyn; Tombeau Cost, Katherine; Tsujimoto, Kimberley C.; Crosbie, Jennifer; Charach, Alice; Anagnostou, Evdokia; Birken, Catherine S.; Monga, Suneeta; Kelley, Elizabeth; Burton, Christie L.; Nicolson, Robert; Georgiades, Stelios; et al. (Frontiers in Sports and Active Living, 2022)
In Ontario, Canada, school extracurricular activities and sports were modified or canceled for a prolonged period due to public health restrictions resulting from the COVID-19 pandemic. The present study aims to examine the association of changes to extracurricular and sport participation and child and youth mental health. Data were collected on child and youth mental health symptoms (n = 908) and participation in extracurricular activities and sports in the 2019–2020 and 2020–2021 academic years. Results indicated that pre-COVID (2019–2020) participation in either extracurricular activities or sports was associated with reduced anxiety, inattention, and hyperactivity during the pandemic (β range −0.08 to −0.11, p < 0.05). Participation in either extracurricular activities or sports during-COVID (2020–2021) was associated with lower depressive symptoms (β range −0.09 to −0.10, p < 0.05). Findings suggest that participation in extracurricular activities and/or school sports both before or during the COVID-19 pandemic were associated with better mental health outcomes in children and youth. Implications of this work consider future situations where restrictions on extracurricular and sport participation are reinstated and the impact of child and youth mental health.